Ruptured MCA Aneurysm Mimicking MCA Territory Ischemic Stroke: A Case Report and Review of the Literature - De Trizio, Ignazio; Reinert, Michael; Robert, Thomas (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Intracerebral hemorrhage (ICH) can be considered one of the major neurologic and neurosurgical emergencies that need a time-dependent diagnosis and treatment. On rare occasions, an aneurysmal rupture may also present with isolated ICH without subarachnoid hemorrhage. We present the case of a 48-year-old woman presenting in our neurosurgical department with ICH and a right middle cerebral artery (MCA) occlusion that, 6 weeks after the initial surgical management, unveiled a large MCA aneurysm treated with a clipping. In this study, we discuss our hypothesis about the etiology and the pathophysiology of this rare phenomenon in the light of the literature in the field.
Keywords: intracerebral hemorrhage; ischemic stroke; MCA aneurysm; differential diagnosis